Rancang Bangun Pengatur Suhu dan Sirkulasi Udara di Smoking Room - Ahmad Syahril Muharom (Ultima Computing : Jurnal Sistem Komputer, 2017)
In this study, the application of temperature and air circulation control in the smoking room using a microcontroller. The Sensors applied to this Prototype are LM35 and DT-Sense CO. The method used design a controller and then apply it to the microcontroller. The sensor has been tested on a miniature smoking room. The results show sensors can work and good, although cigarette smoke and the temperature of the room changes, so air quality in the smoking room can be maintained. Index Term-Cigarette smoke, CO, automation, microcontroller, temperature sensor, smoke sensor